CLASSES SOCIAIS E CONSTRUÇÃO DA HEGEMONIA DAS CLASSES SUBALTERNAS - Franci Gomes Cardoso (Universidade Federal do Maranhão, 2018)
It addresses central analytical categories of Gramsci’s thinking and Marxist tradition (Social Classes, Subaltern Classes, Hegemony and Social Transformation) by reconstructing them in the historic-conceptual configuration of the object of study: Social Classes and Construction of the Hegemony of the Subaltern Classes. Part of the premise inspired fundamentally in Gramsci’s view: it is a historical requirement of the process of social transformation to break the subaltern classes with the dominant ideology and the construction of a conception of their own world that forms the basis of vital actions. This premise constitutes the guiding gaxis for there construction of the object of this study.